2007
DOI: 10.1111/j.1365-2966.2007.11769.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and spectroscopy of ultrasteep spectrum radio sources

Abstract: We present a sample of 40 ultrasteep spectrum (USS; α − 1.3, S ν ∝ ν α ) radio sources selected from the Westerbork in the Southern Hemisphere (WISH) catalogue. The USS sources have been imaged in K band at the Cerro Tololo Inter-American Observatory (CTIO) and with the Very Large Telescope (VLT) at Cerro Paranal. We also present VLT, Keck and William Herschel Telescope (WHT) optical spectroscopy of 14 targets selection from four different USS samples. For 12 sources, we have been able to determine the redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Most of the currently known radio galaxies at z > 4 display a compact steep radio spectrum, with curvature occurring at low observed frequencies (∼100 MHz), data which Klamer et al did not have for their sample. Bornancini et al (2007) also confirm the presence of curvature at low MHz frequencies for their USS sample.…”
Section: The Origin Of the α– Correlation In Flux‐limited Samplessupporting
confidence: 63%
“…Most of the currently known radio galaxies at z > 4 display a compact steep radio spectrum, with curvature occurring at low observed frequencies (∼100 MHz), data which Klamer et al did not have for their sample. Bornancini et al (2007) also confirm the presence of curvature at low MHz frequencies for their USS sample.…”
Section: The Origin Of the α– Correlation In Flux‐limited Samplessupporting
confidence: 63%
“…(a) Despite the fact that most previous searches are limited to sources with spectral index steeper than 1.3, the median spectral index of known HzRGs is 1.31. (b) Though Klamer et al (2006) have shown that the spectra for the majority of HzRGs are straight over a large frequency range, evidence for spectral curvature cannot be ruled out completely (Bornancini et al 2007). This means that at frequencies as low as 150 MHz, a higher cut‐off in the spectral index will translate into even higher cut‐off at the rest frame of high‐redshift objects.…”
Section: Resultsmentioning
confidence: 99%
“…Using data from the VLSS, the 352‐MHz Westerbork in the Southern Hemisphere Survey (WISH; De Breuck et al 2002b) and NVSS, Bornancini et al (2007) found significant curvature below 352 MHz in a subset of 12 USS sources with α 1400 352 ≤−1.3 (WISH–NVSS selection, see Table 9): the median values of the two‐point spectral indices are and . We can test whether we see the same amount of curvature in the MRCR–SUMSS sample over a similar frequency range by using our 74, 408 and 1400 MHz data.…”
Section: Discussionmentioning
confidence: 99%